Dufan (Dunia Fantasi) Ancol di Era Pandemi Covid-19 - Dewi Ayu Kusumaningrum; Ramon Hurdawaty (STIEPAR YAPARI Bandung, 2021)
The enactment of government policies to stop the spread of the virus, requires DUFAN to face new habitual adaptation situations by implementing health protocols, devising various strategies to ensure visitors even if limited movement can still have fun safely. This research discusses the adaptation efforts of tourist objects in the face of the COVID-19 pandemic. It is hoped that this research can become input in planning the adaptation of tourist destination. The qualitative research method used purposive sampling, the collection technique used triangulation (combined) and inductive data analysis. The results of the research are operational observation data of DUFAN, the obstacles faced and the perception of visitors in the pandemic era. DUFAN's operational activities conform to the Taman Impian Jaya Ancol policy. DUFAN's operational reopening was accompanied by various regulations; restrictions on visitors, online ticket reservations, check ticket and body temperature. Availability of hand sanitizer facilities and standing banner for health protocol regulations. There is a surveillance section that always goes around the entire DUFAN area and an environmental disinfection section. The implementation of the health protocol in the operation of game rides is carried out well, however, there are several obstacles faced. The main obstacle is the awareness of visitors about the importance of adhering to health protocols anytime anywhere in the DUFAN area smoking carelessly, not wearing a mask during activities in the DUFAN environment, violation of distance restrictions in queues. The perception of DUFAN visitors in the era of the COVID-19 pandemic was quite good as assessed in terms of operational management systems, online ticket purchases, health protocol information, health protocols for visitors and tourist officers, availability of hand washing facilities, and safety of traveling in DUFAN. Visitors expect more tourist officers at DUFAN to patrol to remind visitors to apply health protocols, especially physical distancing.